1986
DOI: 10.1172/jci112454
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin M antibodies present in the acute phase of Kawasaki syndrome lyse cultured vascular endothelial cells stimulated by gamma interferon.

Abstract: Kawasaki syndrome (KS) is characterized by diffuse vasculitis and marked T cell and B cell activation. In this study, sera from 16 patients with acute KS, 15 patients in the convalescent phase of KS,and 19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
3

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(102 citation statements)
references
References 31 publications
8
91
3
Order By: Relevance
“…Furthermore, a significant positive correlation was observed between titres for IgM AECA and the extent of complement-dependent cytotoxicity. These findings, which are consistent with previous reports [7][8][9], demonstrate that IgM AECA can significantly contribute to vascular injury.…”
Section: Complement-dependent Endothelial Cytotoxicity In Kawasaki DIsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, a significant positive correlation was observed between titres for IgM AECA and the extent of complement-dependent cytotoxicity. These findings, which are consistent with previous reports [7][8][9], demonstrate that IgM AECA can significantly contribute to vascular injury.…”
Section: Complement-dependent Endothelial Cytotoxicity In Kawasaki DIsupporting
confidence: 93%
“…Such differences could be due in part to the time of blood sampling (within 5 days of onset) and the dilution titre (at 1 : 200 for IgG) used here. Leung et al demonstrated that acute KD sera can lyse HUVEC that have been treated with cytokines, including TNF, but do not lyse untreated HUVEC [7,8]. The authors speculated that the cytotoxic antibodies target antigens on the endothelial cells that are induced by the cytokines [7,8,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because it forms the interface between circulating blood and the vessel wall, the endothelial cell could well be the initial site of vascular damage. Anti-endothelial cell antibodies (AEA) have been reported to occur in various diseases (3)(4)(5)(6). We have developed a radioimmunoassay (RIA) to investigate the presence of AEA in rheumatoid vasculitis.…”
Section: Antiendothelial Cell Antibodies In Patients With Rheumatoidmentioning
confidence: 99%